PENGEMBANGAN MEDIA PEMBELAJARAN MONOPOLI UNTUK MENINGKATKAN MINAT BELAJAR GEOGRAFI SISWA - Maya Siskawati; Pargito Pargito; Pujiati Pujiati (Faculty of Teacher Training and Education, University of Lampung, 2016)
The purpose of this research is to produce an output in term of monopoly media and to know how far is the effectiveness of monopoly media to increase students interest in learning Geography. The research method used is Research and Development (RD) which is using ASSURE development design The results of research and development experts validation show after the revised is done on display media aspect in terms of the attractiveness of the image and color clarity of the product it is stated eligible to be used as a medium of learning geography. The test results interest in learning geography experimental class using the media monopoly is higher than the control class that uses a conventional method. Coefficient value t arithmetic amounted to 20.878 and t table of 1.675. So learning by using media monopoly Geography is effective to improve student interest in learning Geography.Penelitian ini bertujuan untuk menghasilkan produk berupa media monopoli dan mengetahui sejauh mana efektivitas media monopoli untuk meningkatkan minat siswa belajar Geografi. Metode penelitian yang digunakan adalah Research and Development (RD) yang menggunakan desain pengembangan ASSURE Hasil penelitian dan pengembangan menunjukkan bahwa: 1) validasi ahli menyatakan produk menarik dan layak untuk digunakan sebagai media pembelajaran Geografi, 2) hasil uji kelompok kecil, besar dan lapangan menunjukkan hasil tes minat belajar Geografi kelas eksperimen yang menggunakan media monopoli lebih tinggi dari pada kelas kontrol yang menggunakan metode konvensional. Nilai koefisien t hitung sebesar 20,878 dan t tabel sebesar 1,675. Sehingga pembelajaran dengan menggunakan media monopoli efektif untuk meningkatkan minat belajar Geografi siswa.Kata kunci: media monopoli, minat belajar geografi, pengembangan